Local responses to tourism development on the North-Eastern coast of Brazil: the case of the municipality of Maragogi in Alagoas State - de Almeida Rocha Kaspary, Manuela Grace; Medeiros de Araujo, Lindemberg (Scientia Plena, 2013)
<!--StartFragment--> In an era in which tourism has gained increasing importance for local/regional development, Brazil's Ministry of Tourism (MTur) has created innovative policies to tourism development and planning, with an implementation focus on the coast of the country. The MTur’s mission states clearly that its aim is to develop tourism as a sustainable economic activity, focused on the creation of jobs and earnings of hard currency, contributing to the promotion of social inclusion. As the North-East region of the country pioneered some of such policies, there has been massive tourism development along the coast of this region. This paper investigates tourism development in the north coast of the state of Alagoas where a 103km-long reef barrier works as the main tourist attractor, with direct influence on land-use and social development. This paper uses spatial and local development theories as a framework to understand the impacts of tourism growth both on the territory and society in Alagoas with an emphasis on the municipality of Maragogi, Alagoas's second most important tourist destination. Methods include interviews with local residents and public officials, observation, photographic survey, and examination of Google Earth images. Findings reveal that there have been different spatial and development responses to tourism in three different parts of Maragogi. Historical land-use patterns and varying capacities of residents to exploit tourism as an economic activity are the two main causes for the variations in the local responses to tourism development in this coastal municipality. <!--EndFragment-->